2021
DOI: 10.3233/jad-200893
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Zonisamide in Dementia with Lewy Bodies Patients with Parkinsonism: A Post Hoc Analysis of Two Randomized, Double-Blind, Placebo-Controlled Trials

Abstract: Background: Although previous phase II and III clinical trials conducted in Japan showed that zonisamide improved parkinsonism in patients with dementia with Lewy bodies (DLB), some differences in efficacy outcomes were observed between the trials. Objective: We aimed to further examine the efficacy and safety of zonisamide in DLB patients with parkinsonism in a post hoc analysis of pooled data from the previous phase II and III trials. Methods: Both trials featured a 4-week run-in period followed by a 12-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
2
1
Order By: Relevance
“…The results of this post hoc analysis indicate that zonisamide 25 mg and 50 mg decreased the axial symptom score compared with placebo and may therefore improve axial symptoms in DLB with parkinsonism. Although PIGD alone did not significantly decrease with zonisamide in a previous report [ 12 ], in this study, zonisamide improved overall axial symptoms as assessed by PIGD- and other axial symptom-related items in UPDRS Part III. Improving axial symptoms may contribute to the reduction of frequency of falls, and no clinical trial to date has evaluated the effect of zonisamide on axial symptoms in patients with DLB.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…The results of this post hoc analysis indicate that zonisamide 25 mg and 50 mg decreased the axial symptom score compared with placebo and may therefore improve axial symptoms in DLB with parkinsonism. Although PIGD alone did not significantly decrease with zonisamide in a previous report [ 12 ], in this study, zonisamide improved overall axial symptoms as assessed by PIGD- and other axial symptom-related items in UPDRS Part III. Improving axial symptoms may contribute to the reduction of frequency of falls, and no clinical trial to date has evaluated the effect of zonisamide on axial symptoms in patients with DLB.…”
Section: Discussioncontrasting
confidence: 91%
“…Given that axial symptoms can be attributed to dysfunction in non-dopaminergic systems [ 13 ], we hypothesized that zonisamide may also improve axial symptoms in this patient population. Although postural instability and gait disorder (PIGD; UPDRS Part III items 29 [gait], and 30 [postural stability]) did not significantly decrease in the zonisamide groups in the previous study [ 12 ], there are several characteristics and important items pertaining to axial symptoms, in addition to those related to PIGD, which may also be associated with fall risk. Therefore, the current post hoc analysis of pooled data from the phase 2 and phase 3 trials was conducted to examine the effect of zonisamide 25 or 50 mg on axial symptoms as assessed using relevant items from UPDRS Part III.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The adjusted mean changes from the baseline MDS-UPDRS Part III total score at 16 and 24 weeks in the zonisamide add-on group (-6.3 and -4.4) were similar to previous reports, with a decrease in treatment effect from 16 to 24 weeks [21,30,36]. However, the percentage of responders with ≥10% improvement at 24 weeks (44%) in this study was lower than previously reported [20,21,30,36,37], possibly because of zonisamide being less effective at 24 weeks than at 16 weeks (maximum effect), and the patient population having more advanced disease (i.e., 5 points higher than the baseline MDS-UPDRS Part III total scores).…”
Section: Discussionsupporting
confidence: 87%